Mechanical properties and piecewise constitutive model of fine sandstone in mining area of western China - Qing Wang; Dongxiao Zhang; Fei Han; Yongqiang Zhao; Pengfei Zhang; Feng Xiong (Scientific Reports)
Abstract Owing to the differences in sedimentary environments in the mining areas of western China, the mechanical properties of rocks in this region are significantly different from those in the central and eastern regions. Therefore, uniaxial cyclic loading-unloading tests were conducted on fine sandstone found in many roof rocks to study the evolution laws of mechanical properties, deformation characteristics, acoustic emission (AE) parameters, and energy under cyclic loading and unloading conditions. The accumulated residual strain, dissipative energy, acoustic emission cumulative ringing counts, and cumulative energy were introduced to characterize the degree of rock damage. Based on this, a piecewise constitutive model was established for fine sandstone. The results indicate that (1) the cumulative ringing counts and cumulative energy of the AE increase in a stepwise manner with an increase in the cyclic loading and unloading times. Still, there is a sudden increase in the plastic failure and post-peak failure stages. (2) The fine sandstone specimens’ input energy, elastic energy, and dissipative energy density increased nonlinearly during the cyclic loading tests. Owing to the closure of the primary pores in the microfracture compaction stage, dominant matrix deformation in the elastic deformation stage, and development and expansion of cracks in the plastic failure stage, with an increase in the cyclic loading and unloading times, the dissipative energy ratio first decreased and then increased. (3) Based on the tangential modulus, residual strain, and Felicity ratio, fine sandstone’s cyclic loading and unloading stress-strain curves were divided into microfracture compaction, elastic deformation, and plastic failure stages. The piecewise constitutive model of fine sandstone constructed with accumulated AE energy was the closest to the real stress-strain curve of the rock, and the deviations of the peak stress and peak strain from the actual situation were 0.52% and 0.84%, respectively. The research results can provide theoretical support for identifying the degree of rock damage in western mining areas and ensure the safe and efficient development of coal resources.